Effect of low-level laser therapy on dental pain induced by separator force in orthodontic treatment - Seyed Mostafa Abtahi; Seyed Amir Mousavi; Hooman Shafaee; Behrad Tanbakuchi (Wolters Kluwer Medknow Publications, 2013)
Background: Patients undergoing orthodontic treatment experience varying degrees of pain with separator insertion. A survey of patients' attitude towards orthodontic treatment revealed that pain was the most discouraging factor related to their treatment. Moreover, it was the highest ranking reason for wanting to discontinue care. The purpose of this study was to determine the effect of low-level laser irradiation on dental pain induced by forces from separators in orthodontic treatment. Materials and Methods: This study was an experimental clinical trial. Twenty-nine patients were recruited for this research. Low-level laser irradiation was applied on one half of the maxillary and mandibular arches for 5 days. The opposite half of the arches was considered the control group. Laser irradiation was applied for 30 seconds in the alveolar bone between the second premolars, first molars, and second molars. Pain perception was evaluated with a standardized questionnaire that was answered by patients before and after laser irradiation. Data was analyzed by Wilcoxon and Friedman test. P value ≤0.05 was considered significant. Results: The highest pain level was reported at day 1 following separator placement and decreased gradually until day 5. At day 4 and 5, the pain intensity was lower in the laser group than in the control group; however, this finding was not statistically significant. At day 1 and 3, the pain intensity was higher in the laser group than in the control group; however, it was not statistically significant. At day 2, the pain intensity was lower in the laser group than in the control group and was statistically significant. Conclusion: Our findings suggest that there is no statistically significant difference in pain by using low-level laser irradiation.